Idiopathic pulmonary fibrosis: securing a confident diagnosis for every patient. Issue 4 (April 2016) - Jones, Mark G.; Walsh, Simon L.F.; Jones, Kirk D.; Richeldi, Luca
Almost half a century ago Liebow and Carrington [1] proposed their landmark framework to classify the idiopathic interstitial pneumonias (IIPs), a diverse group of diffuse parenchymal lung diseases of unknown aetiology. This classification approach has since informed the principal that in IIP histopathological pattern may have clinical implications including prognosis and treatment. Five subgroups were identified, the most frequent of which was termed "usual" interstitial pneumonia (UIP) and is the pattern which, in the absence of any identifiable cause, is diagnostic of the prototypic chronic progressive fibrotic lung disease idiopathic pulmonary fibrosis (IPF) [2]. Inconsistent UIP pattern on HRCT in patients with suspected IPF should not rule out possibility of an IPF diagnosis http://ow.ly/YcVao